THE FEATURES OF PSYCHOPHYSIOLOGICAL STATE OF SCHOOL AGE CHILDREN WITH LATENT IRON DEFICIENCY AND LIGHT IODINE DEFICIENCY - Шаламай, У. П.; Заяць, О. В.; Воронич-Семченко, Н. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Research results of psychophysiological state of school age children with iodine and iron deficiency, and in healthy coevals, their interconnection with indexes of thyroid system (hormonal status, median of urinary iodine), and iron metabolism (hemoglobin content, level of serum iron, total binding capacity of serum, serum ferritin) are represented in the article.It was determined, that light iodine deficiency is followed by violations of thyroid homeostasis (decreasing of freeT3 – fT3, free Т4 – fT4 content on the phone of elevation of TTH in blood serum), and latent iron deficiency, even under conditions of adequate iodine supply, causes the tendency to changes of thyroid hormones balance. The most significant changes of cognitive functions were found in case of latent iron deficiency, on the phone of light iodine deficiency. In this group of pupilsintelligence quotient is significantly reduced, speed of information processing is decreased, early fatigue is developed, and performance accuracy is reduced, and attention becomes unstable. The combined microelement deficiencypotentiates the changes of examined indexes of cognitive functions.